The influence of coarse aggregate gradation on the mechanical properties, durability, and plantability of geopolymer pervious concrete. (13th June 2023) - Luo, YiPing; Lv, Yurong; Wang, Defa; Jiang, Zhonghua; Xue, Guobin
Highlights: The improvement of aggregate gradation makes geopolymer pervious concrete have higher strength, elastic modulus and energy absorption ability. Metakaolin as a matrix can effectively improve pervious concrete's anti-dry-wet cycle-sulfate corrosion resistance of. Tall fescue and Ryegrass can better adapt to the growth in the pores of geopolymer pervious concrete. Abstract: Different coarse aggregate gradations were used to study the effect on the performance of geopolymer permeable concrete, and physical, mechanical properties and resistance to dry-wet cycle-sulfate erosion and planting tests were carried out. With the improvement of 6–10 mm and 10–15 mm size and particle size in the coarse aggregate gradation, the porosity of permeable concrete decreases, and the compressive strength, energy absorption capacity, and elastic modulus increase. Among them, the porosity and permeability coefficient of the two-graded specimen is the lowest. In the three-graded aggregate, the compressive strength is 11.7 MPa, and the tensile strength is 1.7 MPa. It can be obtained from the test results of the anti-dry-wet cycle-sulfate corrosion test that the mass loss rate of single-graded specimens is the largest, and the third-grade aggregates are smaller. With the increase of aggregate gradation, the compressive strength increased and then began to decrease. In the planting test, Ryegrass and Tall fescue have better germination rates and growth heights, Bermudagrass has poor adaptability.